Cognitive beliefs and positive emotions about change: Relationships with employee change readiness and change-supportive behaviors. (October 2019) - Rafferty, Alannah E; Minbashian, Amirali
Research has focused on individuals' beliefs about change when considering the antecedents of employee change readiness. Our study is unique as we identify beliefs and positive emotions about change as proximal antecedents of change readiness. In Study 1, a cross-sectional study of 252 government workers, measures of change beliefs, positive emotions about change and change readiness were developed and tested. Study 1 examined relationships between these constructs. In Study 2, we collected data at two time points separated by 3 months from 199 employees. Study 2 examined the direct and indirect relationships among change beliefs, positive emotions about change, change readiness and change-supportive behaviors. Structural equation modeling results provided support for the validity of our measures. In both studies, cognitive beliefs about change and positive emotions about change were significantly associated with change readiness. Study 2 provided support for indirect and direct relationships between change beliefs and positive emotions and change behaviors. An implication of this research is that failure to consider positive emotions about change means ignoring a key source of variation in change readiness. Practically, results suggest a need to develop both change beliefs and positive emotions about change to enhance employees' change readiness and change-supportive behaviors.